If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 14 + 3n = -2j + 6 Reorder the terms: 14 + 3n = 6 + -2j Solving 14 + 3n = 6 + -2j Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-14' to each side of the equation. 14 + -14 + 3n = 6 + -14 + -2j Combine like terms: 14 + -14 = 0 0 + 3n = 6 + -14 + -2j 3n = 6 + -14 + -2j Combine like terms: 6 + -14 = -8 3n = -8 + -2j Divide each side by '3'. n = -2.666666667 + -0.6666666667j Simplifying n = -2.666666667 + -0.6666666667j
| 15y=19y-7 | | 8q-38-11=29 | | a^2+b^2=89 | | 2c^3+14c-36c=0 | | -5(9-11x)+8x-10=9x-12 | | m=4-(-2)/-2-(-4) | | -2-c=(-1) | | 16m-4s+7m-6s= | | 9x^2+6x+3x=72-2+13x | | -8x-6+2w=-2+w | | 5p+10+4p=-35 | | x=x/2+x/3-2 | | x/-8=17(-5) | | (x+3)(x+3)=5 | | -12(x+3)+x+15=4-13x | | 7log(2x-20)=14 | | 16m-4m+7m-6s= | | 7x-(2x+4)=2x+(x-3)+3 | | 0,4+5=0,6z+0,6 | | 11p+13-8p=-17 | | 12/11 | | .25x=0 | | 36=r/6 | | -33=-36-6x+6 | | 9x^2+3x-5= | | -3.2x=-52.36 | | -33=-3x-6x | | 75-37= | | -8+2(3x+5)=-5+(x-4)+8x | | X+85+40=180 | | 3.2x=-52.36 | | 4(9+5m)-7m= |